KEPEMIMPINAN TRANSFORMASIONAL DALAM MANAJEMEN SUMBER DAYA MANUSIA (STUDI KASUS APARATUR SIPIL NEGARA PEMERINTAH KOTA KUPANG NUSA TENGGARA TIMUR) - Riwukore, Jefirstson Richset; Alie, Marzuki; Habaora, Fellyanus (Universitas Indo Global Mandiri Palembang, 2021)
The purpose of this research was to measure the principles of transformational leadership in human resource management. This research was conducted for 7 (seven) months from September 2019 to February 2020 at the Regional Government Secretariat of Kupang City (Pemkot Kupang) East Nusa Tenggara (NTT) Indonesia. The population of respondents in this study were the State Civil apparatus (ASN) within the scope of the Kupang City Government, East Nusa Tenggara, group I to group IV, totaling 370 ASN Kupang City government consisting of ASN group I as many as 8 of respondents, ASN group II as many as 80 of respondents, group III as many as 215 of respondents, and group IV as many as 67 of respondents. The type of data in this study consists of primary data and secondary data. The analysis used in this research is descriptive analysis with data processing and analysis using a Likert scale. The results showed that the transformational leadership within the City Government by policy makers has generally been implemented well. This can be seen from the ability to build a vision, inspirational communication, leaders who provide support, increase in intellectual abilities, and respect for individuals.Â Keywords: transformational leadership, state civil apparatus, Kupang City Government